The Association Between Self-Care and Quality of Life Among Iranian Older Adults: Evidence from a Multicenter Survey - Hassan Soleimanpour; Saber Ghaffari-fam; Ehsan Sarbazi; Raheleh Gholami; Hosein Azizi; Masumeh Daliri; Saman Sedighi; Hossein-Ali Nikbakht; Layla Shojaie; Ali Allahyari (Shiraz University of Medical Sciences, 2024)
Background: The growing number of aging people, ensuring their quality of life (QoL), and the social services designed for this population group are becoming increasingly significant concerns. This study explored how socioeconomic status and self-care affect older adults' QoL. Methods: This cross-sectional study included 322 older people living in Tabriz in 2021. The subjects were recruited using a multi-stage sampling method. Older persons were asked to complete the Socio-Economic Status (SES) questionnaire, the Self-Care Behavior Questionnaire, and the Iranian version of the 12-item Short Form Health Survey (SF-12). Results: A hierarchical logistic regression analysis model was used to investigate the factors influencing QoL. The regression analysis showed that marital status, social self-care, and self-care during illness significantly impacted the older person's quality of life (p < 0.05). Twenty-nine and twenty-seven percent of the variance in the mental and physical health dimensions, respectively, were predicted by the variables included in the model.Conclusion: Promoting social self-care and self-care during illness had a positive relationship with the QoL of older persons. These results can serve as a reference for future studies pertinent to self-care for older adults.